Peran Mahasiswa Magang (MBKM) dalam Meningkatkan Efektivitas Pelayanan Pajak Daerah Lainnya di BPPRD Kota Palangka Raya - Afia Nurafifah; Haidi Hajar Widagdo; Desira Albertine (Politeknik Kampar, 2025)
Abstract: This article discusses the role of student interns through the Merdeka Belajar Kampus Merdeka (MBKM) program in improving the effectiveness of other regional tax services at the Regional Tax and Retribution Management Agency (BPPRD) of Palangka Raya City. This study uses a descriptive method based on direct experience during a four-month internship. Students are actively involved in inputting taxpayer data, recording the receipt agenda, and observing the tax service process such as restaurants, hotels, parking, entertainment, and swallow's nests. The results show that student involvement can lighten the workload of staff in other regional tax services. This activity not only provides direct work experience to students but also has a positive impact on public services in government agencies. Keywords: MBKM Internship, Regional Tax Services, Student Contributions Abstrak Artikel ini membahas peran mahasiswa magang melalui program Merdeka Belajar Kampus Merdeka (MBKM) dalam meningkatkan efektivitas pelayanan pajak daerah lainnya di Badan Pengelola Pajak dan Retribusi Daerah (BPPRD) Kota Palangka Raya. Penelitian ini menggunakan metode deskriptif berdasarkan pengalaman langsung selama magang empat bulan. Mahasiswa terlibat aktif dalam penginputan data wajib pajak, pencatatan agenda penerimaan, serta observasi terhadap proses pelayanan pajak seperti restoran, hotel, parkir, hiburan, dan sarang burung walet. Hasilnya menunjukkan bahwa keterlibatan mahasiswa dapat meringankan beban kerja staf di bidang pelayanan pajak daerah lainnya. Kegiatan ini tidak hanya memberikan pengalaman kerja langsung kepada mahasiswa, tetapi juga berdampak positif terhadap pelayanan publik di instansi pemerintah.